2016
DOI: 10.1038/srep38389
|View full text |Cite
|
Sign up to set email alerts
|

Foldable and Disposable Memory on Paper

Abstract: Foldable organic memory on cellulose nanofibril paper with bendable and rollable characteristics is demonstrated by employing initiated chemical vapor deposition (iCVD) for polymerization of the resistive switching layer and inkjet printing of the electrode, where iCVD based on all-dry and room temperature process is very suitable for paper electronics. This memory exhibits a low operation voltage of 1.5 V enabling battery operation compared to previous reports and wide memory window. The memory performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…We found that the IL reduces the surface roughness of the TaO x and enhances the interface quality at the bottom interface layer (Figure S6); thus, improving the durability of the device. 49 Moreover, the insertion of the AlN layer also improves the adhesion of the films; we conducted a peeling test using a scotch tape, and the result shows that the AlN has better mechanical adhesion on the ITO substrate than TaO x (Figure S7). In order to further assess the feasibility of the DL device for wearable electronics that may not only be used in indoor environments but also outdoors, the UV stability of the device would be investigated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We found that the IL reduces the surface roughness of the TaO x and enhances the interface quality at the bottom interface layer (Figure S6); thus, improving the durability of the device. 49 Moreover, the insertion of the AlN layer also improves the adhesion of the films; we conducted a peeling test using a scotch tape, and the result shows that the AlN has better mechanical adhesion on the ITO substrate than TaO x (Figure S7). In order to further assess the feasibility of the DL device for wearable electronics that may not only be used in indoor environments but also outdoors, the UV stability of the device would be investigated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Paper is an intimate and ubiquitous material in our daily activities. In recent years, paper has been considered to be cheap; thus, it is a promising substrate for flexible electronics. , Paper-based flexible devices are gaining increasing attention as cost-effective, eco-friendly, lightweight, and disposable electronics for wearable applications. For decades, there have been many studies on the integration of electronic components, such as interconnections, transistors, diodes, inductors, memories, sensors, and energy harvesting/storage devices into paper substrates. Moreover, origami- and kirigami-inspired device structuring can allow the fabrication of ultra-stretchable paper-based electronics exhibiting a stretchability of over 1000%. …”
Section: Introductionmentioning
confidence: 99%
“…Paper-based, foldable and disposable memory with a low voltage operation of 1.5 V has been shown, 101 which would allow for on-board battery operation if integrated as part of an ASSURED paper-based device. Additionally, memory performance was maintained up to 100 s of switching cycles after folding tests were carried out, showing robust and repeatable characteristics that align well with the ASSURED principles.…”
Section: Data Processing and Storagementioning
confidence: 99%